Effective genome editing and identification of a regiospecific gallic acid 4-O-glycosyltransferase in pomegranate (Punica granatum L.). Issue 1 (8th November 2019) - Chang, Lijing; Wu, Sheng; Tian, Li
Abstract: Pomegranate ( Punica granatum L.) trees are woody perennials that bear colorful and nutritious fruits rich in phenolic metabolites, e.g., hydrolyzable tannins (HTs) and flavonoids. We here report genome editing and gene discovery in pomegranate hairy roots using Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) (CRISPR/Cas9), coupled with transcriptome and biochemical analyses. Single guide RNAs (sgRNAs) were designed to target two UDP-dependent glycosyltransferases (UGTs), Pg UGT84A23 and Pg UGT84A24, which possess overlapping activities in β-glucogallin (a galloylglucose ester; biosynthetic precursor of HTs) biosynthesis. A unique accumulation of gallic acid 3- O - and 4- O -glucosides (galloylglucose ethers) was observed in the PgUGT84A23 and PgUGT84A24 dual CRISPR/Cas9-edited lines (i.e., ugt84a23 ugt84a24 ) but not the control (empty vector) or PgUGT84A23/PgUGT84A24 single edited lines ( ugt84a23 or ugt84a24 ). Transcriptome and real-time qPCR analyses identified 11 UGTs with increased expression in the ugt84a23 ugt84a24 hairy roots compared to the controls. Of the 11 candidate UGTs, only Pg UGT72BD1 used gallic acid as substrate and produced a regiospecific product gallic acid 4- O -glucoside. This work demonstrates that the CRISPR/Cas9 method can facilitate functional genomics studies in pomegranate and shows promise for capitalizing on the metabolic potential of pomegranate for germplasm improvement.